Highly-porous metal option for primary cementless acetabular fixation. What is the evidence?. Issue 6 (November 2013) - Banerjee, Samik; Issa, Kimona; Kapadia, Bhaveen H.; Pivec, Robert; Khanuja, Harpal S.; Mont, Michael A.
The purported improvement in the initial stability and enhanced osseointegration has stimulated a recent increase in the use of highly-porous interfaces for acetabular fixation in cementless hip arthroplasty. The aim of this study was to comprehensively review the literature and report the clinical outcomes of highly-porous metals in primary cementless acetabular fixation. Aseptic survivorship, osteolysis, Harris hip scores, cup migration and the incidence of peri-acetabular gaps, and peri-prosthetic fractures were assessed. A search of four electronic databases yielded 16 level IV studies that reported on the use of these newer highly-porous metals in primary cementless acetabular fixation. The mean cup-survivorship for aseptic loosening with the use of these modern interfaces was 100% and the mean acetabular component revision rate for any reason at 100-component years was 0.14 (range 0 to 0.55) at a mean follow-up of five years. The functional outcomes were also noted to be excellent with significant improvement in Harris Hip scores from a mean of 46 points pre-operatively (15 to 85 points) to 91 points (range, 80 to 97 points) post-operatively. Cup-stability was found to be excellent with a mean incidence of migration of less than 2% at mean follow-up of five years (range, 0.6 to 12 years). None of the studies on primary arthroplasty had any evidence of progressive peri-acetabular osteolysis in their study population at final follow-up. In summary, randomised controlled trials and long-term evaluation of these highly-porous implants will be needed in future to determine their potential superiority and to justify the increased cost.